THE USE OF FLASHCARD IN ENGLISH VOCABULARY LEARNING - Arsana Anak Agung Putu; Putri Maharani Anak Agung (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2021)
Vocabulary plays an important role in oral and written communication of foreign language (Laufer and nation,1999). Vocabulary is one of the language aspects that is very pivotal in English learning. If we have less vocabulary, we will not clearly enough to gain the information in communication. The language learning approach using flashcards provides an effective training and learning method for teachers, and flashcards can also be used effectively as teaching resources to help students learn and understand vocabulary. One of the main advantages of flashcards is, they can be carried anywhere and can be studied at any time (Brown, 2000). Flashcards are a fun strategy and can increase students' reading interest. This study is a library research which aimed to describe the use of flashcard in English vocabulary learning. The method used in this research is the study of literature. The results showed that the use of the flashcard strategy in English vocabulary learning at the elementary school and high school levels were preferred and interested in using flashcards equipped with various images and has a variety of colors. Moreover, flashcards also make students more active and they did not get bored easily when learning English vocabulary.